African American Parents With Children With Disabilities: Gathering Home–School Reflections. (November 2021) - Brandon, Regina R.; Higgins, Kyle; Jones, Vita L.; Dobbins, Nicole
African American families are multidimensional entities that change over time. This is particularly true when there is a child with a disability in the family. The communication and interaction of the family and parents with the teachers and school in which their child receives special education services are of crucial importance. The goal for all is a relationship based on equity and parity, but research indicates that often this is not the case for African American parents who have a child with a disability. Based on a review of the literature focused on African American parents with a child with a disability and their sense of alienation from their child's school, a questionnaire is presented in which parents reflect on the barriers in five categories identified in the literature (e.g., personal concerns, work concerns, lack of interest, logistical concerns, teacher/parent relationships) that may impede the development of a professional partnership with the individuals who provide special education services to their child. The questionnaire is presented and suggestions for its usage are provided.